Penatalaksanaan Fisioterapi Pada Kasus Post Operasi Fraktur Patella Sinistra Di RSUD Soehadi Prijonegoro Sragen - Aji Bayu Pamungkas, Iyan, Yulisna Mutia Sari, SSt.FT,M.Sc (GRS) (2015)
At the present time, increasing number of motor vehicles or cars can increase risk an accident. One as a result of accidents on the road it a fracture patella sinistra. physiotherapy management to patient post surgery fracture patella sinistra can be done with infra red modulation and therapeutic exercise as hold relaxes active free movement, assisted active movement and the passive exercise. The purpose of this research was to know benefits of using infra red therapy and therapy exercise can reduce pain in knee joint , quadriceps and increase oower of hamstring, reduce odema incise, reduce spasm in the hamstring and quadriceps and increase activity functional of patients post surgery patella sinistra Method of research with case of Mr. .R post surgery fracture patella sinistra with diskriptive analysis. Modulation infrared and therapy exercise six times.The assessment odema first day until the lateral condilus to proximal to 40 cm.Third day to 35 cm and six days to 34 cm.The lateral condilus the distal fell 10 cm obtained data on the first of the 35 cm, third day of the 33 cm, and on the sixth day the 31 cm.The pain is measured using the vase and we get the results of the tenderness and pains of T1 - T6. At T1, tenderness 4 to decline to 3 in 1 on t2 and T5 and T6.The pain of his left knee at the flexion of 7 and narrowed to 2 in T6. Spasm of complaints first to second day there were spasm of weight. The third day until the fourth day spasm of decline in the moderate .The fifth day and the sixth day decrease spasm of being light and in the seventh day there was no spasm . Muscular strength first to third day, quadriceps muscle power and hamstring 3 grade.On the fourth and fifth day to 4 and on sixth and seventh increased to 5. LGS first day of the ability of Lgs active 60o , increase in the third day to 70 o , the seventh day of 120o. LGS passive in first day of 70o, and continues up to seventh day in 120o. Conclusions giving therapy after six times, complaints on odema, pain.Spasm. can reduce, increasing power of quadriceps muscle, and hamstring and by the scope of the knee joints of active and passive could increase.